COMMUNITY EMPOWERMENT THROUGH STUNTING PREVENTION AND MSME BUSINESS LEGALITY: A CASE STUDY OF KKN IN MEKARMULYA VILLAGE - Diky Dikrurrahman; Fadhli Dzil Ikram; Gilar Giri Prayoga Putra; Alfin Mubarok; Widya Patra Nurisma Septi (Ann Publisher, 2025)
Abstract Background. The Real Work Lecture Program (KKN) in Mekarmulya Village aims to improve the welfare of the community through two main approaches, namely health and economy. Aims. In terms of health, the program is focused on socializing stunting prevention, which includes balanced nutrition education, basic health checks, and healthy lifestyle training for pregnant women and toddlers. Meanwhile, in the economic aspect, assistance is provided for Micro, Small, and Medium Enterprises (MSMEs) in making Taxpayer Identification Numbers (NPWP) and Business Identification Numbers (NIB) as the first step in business legality. Methods. This program uses methods such as socialization, direct assistance, and cooperation with health workers and related agencies. The results show that the people of Mekarmulya Village increasingly understand the importance of balanced nutrition in stunting prevention. Result. In addition, in the business legality assistance program, as many as 21 people participated in this activity, with six people successfully making NPWP and 15 people obtaining NIB. This shows that more and more MSME actors know the importance of business legality for their business development. Conclusion. Furthermore, this program has a close relationship between health and economics. With the increase in the legality of MSME businesses, it is hoped that the economic welfare of the community will also increase, which can ultimately impact meeting family nutritional needs and supporting efforts to prevent stunting in a sustainable manner. Implication. Thus, the program provides not only short-term benefits but also creates a sustainable positive impact on society.